Co-Branding: A Case Study of Micromax and MTV - Mehdi, Mokhalles M. (Indian Journal of Marketing, 2013)
Co-branding is an instrument to introduce new products in the market by partner brands. The aim of the present case study is to identify the usefulness of co-branding in brand building. Partner selections in co-branding as well as the pessimistic side of co-branding have also been included in the present research. The paper also discusses the role of co-branding with the help of Micromax and MTV case study. The study analyzes why partner selection is an important aspect in co-branding. Proper partner selection increases the brand equity of each partner. The study also discusses the advantages and disadvantages of co-branding. The research concludes that companies are adopting co-branding as an extension strategy to maintain and to gain the market share by introducing fresh products.